URGENSI AGAMA DAN TEKNOLOGI DALAM KONTEKS MASYARAKAT 5.0 - Romadhon, Muhammad Qomari; Munir, Munir; Karoma, Karoma (Peneliti.net, 2025)
The rapid development of technology in the context of society 5.0 has resulted in significant transformations in the way humans interact, communicate and live social lives. This research aims to explore the complex relationship between religion and technology in modern society, focusing on how these two elements can collaborate to create a more inclusive, ethical and sustainable social environment. Specifically, this research has four main objectives: (1) Analyzing the role of religion as a source of life and inspiration in society 5.0, (2) Identifying the function of technology as a tool in creating efficiency and effectiveness, (3) Examining the characteristics of a global society that emerges from interactions across cultures, geographies, and religions, and (4) Evaluating the advantages and disadvantages of technology in the context of society 5.0. The research method used is qualitative with a literature study approach. Data was collected through various academic sources such as books, journals, and relevant scientific articles. The researcher conducted an in-depth analysis by paying attention to the relationship between religion and technology in the context of a modern society that is increasingly connected globally. The results show that religion and technology have great potential to complement each other. Religion provides a moral and ethical foundation, while technology offers tools to improve the quality of life. Research reveals that about 84% of the world's population identifies with a religion, and more than 4.5 billion people are connected via the internet, signaling the complexity of the interaction between these two domains. Key findings show that collaboration between religion and technology can create positive impacts in a variety of areas, including education, social services, intercultural dialog, and addressing humanitarian issues. For example, religious organizations have leveraged technology to disseminate teachings, provide social assistance and facilitate interfaith dialogue. However, the research also identified significant challenges, such as the digital divide, potential misuse of technology, and conflicts between religious traditions and technological innovation. Around 2.9 billion people still do not have internet access, raising concerns about global inequality. In addition, the research also emphasizes the importance of a collaborative approach between religious leaders, technology developers, and communities to create inclusive and sustainable solutions. The research suggests that in the future, the integration between religious values and technological advancements can be the foundation for building a more just, ethical and humane society.